Urban Environmental Management and Governance. Challenges for the 21st Century. - Jacobi, Pedro Roberto; Dias Peres, Ursula (Routledge, 2016)
In the Brazilian metropolitan context, environmental problems have been increasing. The growth of metropolitan areas in recent decades has transformed Brazil into, primarily, an urban country, with 84% of its population living in cities. This, together with a lack of urban management, has led to an increase in floods, inadequate sanitation, difficulties in solid waste management, among other effects harmful to the health of the population. It has also resulted in conflicts and shaped land-use practices, leading to dual cities, where the segregation of the poorer population forces them to settle in places where environmental risks are high. Given this scenario, what factors should be emphasized so as to address urban sustainability? Environmental governance of urban space is key to achieving sustainability and reducing vulnerability to disasters. The concept of environmental governance opens up a stimulating space to rethink innovative management approaches that involve a range of actors, institutions and interrelationships. It also provides an opportunity to reflect on topics, where agents are able to articulate specific arrangements and negotiation possibilities, ensuring that the good common prevails (Jacobi 2012). Thus, this paper aims to address the main difficulties in urban environmental management, and in particular, one of its biggest challenges: intergovernmental integration and the creation of innovative spaces for dialoguing with the various sectors of society.
Keywords: Stadtplanung; Stadtregion; Umweltschutz; Abfallbeseitigung; Wasserwirtschaft; Verkehrsbelastung; Stadtverkehr; technische Infrastruktur; Metropolregion; Regionalmanagement; Regional Governance